2002
DOI: 10.1017/s0021859602002502
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cultivation method and timing, previous sward and fertilizer level on subsequent crop yields and nitrate leaching following cultivation of long-term grazed grass and grass-clover swards

Abstract: A 3-year field experiment was conducted in 1996-98 near Penicuik, Scotland, to investigate the fate of N released after cultivation of previously long-term grass and grass-clover swards. The effects of timing of cultivations (autumn and spring), tillage methods (no tillage, ploughing to 200 mm and ploughing to 300 mm) and fertilizer N for spring (0, 40, 80 and 120 kg N/ha) and winter barley (0, 60, 120, 180 kg N/ha) on yield, N uptake and nitrate leaching were measured.In 1996, after spring cultivation, on plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 10 publications
(21 reference statements)
2
23
0
Order By: Relevance
“…The high field N 2 O fluxes in the 3-month period early in the first season represented a cumulated N loss in the same range as that for annual leaching losses at this site of 6.4-19.6 kg ha À1 (Vinten et al, 2002) and represents 7.4 and 1.9% if the N added as fertilizer. The highest N 2 O fluxes that we measured from the no-tilled treatment were in cores where the pore system was blocked by water.…”
Section: Tillage Crop Cover and Matric Potentialmentioning
confidence: 75%
See 1 more Smart Citation
“…The high field N 2 O fluxes in the 3-month period early in the first season represented a cumulated N loss in the same range as that for annual leaching losses at this site of 6.4-19.6 kg ha À1 (Vinten et al, 2002) and represents 7.4 and 1.9% if the N added as fertilizer. The highest N 2 O fluxes that we measured from the no-tilled treatment were in cores where the pore system was blocked by water.…”
Section: Tillage Crop Cover and Matric Potentialmentioning
confidence: 75%
“…The site is in a cool, moist climate with an average annual rainfall of 866 mm and an excess winter rainfall of 300 mm. Further details of the site and experimental conduct were given by Vinten et al (2002).…”
Section: Study Sitementioning
confidence: 99%
“…Vinten et al [42] determined, in one year of research, higher, and in the other year of research, lower soil C-CO 2 emissions at no-tillage compared to conventional tillage. On the other hand, many other authors did not determine any significant differences in soil C-CO 2 emissions between mentioned tillage treatments [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Franzluebbers et al [26], who found that CO2 emissions in some years were higher in no-tillage than in conventional tillage, but in other years, the tillage effect was not observed. Vinten et al [42] determined, in one year of research, higher, and in the other year of research, lower soil C-CO2 emissions at no-tillage compared to conventional tillage. On the other hand, many other authors did not determine any significant differences in soil C-CO2 emissions between mentioned tillage treatments [43][44][45].…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionsmentioning
confidence: 99%
“…It was assumed that highly responsive arable crops such as winter wheat and potatoes would be grown on soils with greater mineralisation rates, typical of the first Scotland, 199597 year after the ploughing of grass. From experiments on N release to cereals after long term grass, a figure of 70 kg N ha 1 was adopted (Vinten et al, 2002) This simplified representation does not account for differences in N processes as a function of soil type, temperature or the availability of soil N stores and as such will limit the potential of the NIRAMS model for predicting responses to changes in land management.…”
Section: Net N Mineralisationmentioning
confidence: 99%